THE SOCIAL FUNCTION OF SEKARTAJI PARK IN SURAKARTA CITY - Febriarto, Prasetyo (Universitas Aisyiyah Yogyakarta, 2019)
Sekartaji Park in Surakarta City has been directed to public spaces but not fully in accordance with the form of community activities. City parks as a social function accommodate user activities that can improve the quality of city parks. The purpose of this study is to determine the social functions of Sekartaji Park in Surakarta City. The method used is descriptive explorative by analyzing the social functions of user activities that occur outside and inside the park. Research results on the extent to which sekarjati park are used with the conclusion that the social functions that occur show whether quality.